2017
DOI: 10.1186/s13075-017-1407-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen attenuates the spondyloarthritis manifestations of the SKG arthritis model

Abstract: BackgroundAnkylosing spondylitis (AS) is a male-predominant disease, and radiographic evidence of damage is also more severe in males. Estrogen modulates immune-related processes such as T cell differentiation and cytokine production. This study aimed to evaluate the effect of estrogen on the disease activity of spondyloarthritis (SpA).MethodsThe effects of estrogen on the development of arthritis were evaluated by performing ovariectomy and 17β-estradiol (E2) pellet implantation in zymosan-treated SKG mice. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 40 publications
0
33
1
Order By: Relevance
“…However, a more recent study showed neither difference in onset nor severity in 571 female AS patients, of which 448 women had used oral estrogen therapy and 123 did not [ 39 ]. In a study with a mouse model, the female mice with high estrogen levels had significantly less severe arthritis and SpA manifestations (such as spondylitis, enthesitis, and bowel inflammation) compared to mice with low estrogen levels [ 38 ]. In a review and case-control study of 50 males and 10 female AS patients, Giltay et al [ 42 ] described that serum testosterone levels were not elevated in AS patients compared to controls and did not seem to influence progression of AS [ 41 ].…”
Section: Immunology and Geneticsmentioning
confidence: 99%
“…However, a more recent study showed neither difference in onset nor severity in 571 female AS patients, of which 448 women had used oral estrogen therapy and 123 did not [ 39 ]. In a study with a mouse model, the female mice with high estrogen levels had significantly less severe arthritis and SpA manifestations (such as spondylitis, enthesitis, and bowel inflammation) compared to mice with low estrogen levels [ 38 ]. In a review and case-control study of 50 males and 10 female AS patients, Giltay et al [ 42 ] described that serum testosterone levels were not elevated in AS patients compared to controls and did not seem to influence progression of AS [ 41 ].…”
Section: Immunology and Geneticsmentioning
confidence: 99%
“…We investigated the effect of SERM Laso on the disease activity of SpA. We previously reported that estrogen attenuates disease activity of SpA using an animal models [7]. In this study, we demonstrated that SERM, like estrogen, suppressed joint in ammation and increased BMD.…”
Section: Discussionmentioning
confidence: 70%
“…Eight-week-old female SKG mice underwent an ovariectomy under anesthesia 2 weeks before arthritis induction. One week later after ovariectomy, slow-releasing pellets of E2 (0.72 mg, 60 days release; Innovative Research, Sarasota, FL, USA) were implanted subcutaneously on the neck scruff of mice in the E2-treated group [7,12]. For continuous Laso delivery, subcutaneously implanted ALZET® osmotic pump (Alza Corp., Palo Alto, CA, USA) technique was used.…”
Section: Lasofoxifene or 17β-estradiol (E2) Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These mice are generated on a BALB/c genetic background and spontaneously develop autoimmune arthritis that resembles human RA [ 24 , 31 ]. Similar to CIA, SKG arthritis is dependent on proinflammatory cytokines such as IL-6 and particularly IL-17 [ 32 35 ]. SKG CD4 T cells that were deficient in IL-17 failed to induce arthritis upon adoptive transfer into RAG2-deficient mice, while the induction of arthritis was accelerated by the transfer of IFN- γ -deficient CD4 T cells [ 35 ].…”
Section: Animal Models Of Experimental Arthritis and Th17 Cellsmentioning
confidence: 99%